Yield, average weight and number of okra fruits depending on the variety during cultivation in the conditions of the Right-bank Forest-Steppe of Ukraine - Хареба, В. В.; Унучко, О. О. (Scientific Progress & Innovations, 2017)
Okra is an unconventional vegetable crop, which has become widely spread in the world, it is annual, thermophilic plant has not only nutritional value, but is also used as a medicinal plant, so far as it has vitamins and nutrients in its composition. The influence of the variety on the formation of commodity fruits, their mass and the yield of plants of okra is examined. The yield of okra varieties on average during the years of research varied within the range of 9.0–5.7 t/ha. In the zone of the Right-bank Forest-Steppe, the highest yield was produced by the Yunona variety – 8.6 t/ha, which exceeded the control by 1.1 t/ha, and the lowest yield was Mestnyi 1 – 6.0 t/ha, 5 t/ha less than in the control version.